The Principle of Professionalism of the State Civil Apparatus in Public Service - M. Riyanto; Ernesta Arita Ari; Johannes Triestanto; Iwan Rasiwan; Bambang Supriadi (Universitas Muhammadiyah Palu, 2026)
The professionalism of the State Civil Apparatus (Aparatur Sipil Negara/ASN) constitutes a fundamental principle in the implementation of public services that prioritize societal interests. ASN are not merely responsible for executing government policies, but also serve as the frontline actors in delivering public services that are effective, efficient, transparent, and equitable. This article aims to examine the principle of ASN professionalism in public service delivery in Indonesia, as well as the factors influencing it within the framework of bureaucratic reform and increasingly complex public demands. The research employs a qualitative approach using a literature review method, analyzing national scientific journals, statutory regulations, and other relevant literature related to ASN professionalism and public service. The findings indicate that ASN professionalism is not an isolated concept, but is shaped by several key factors, including human resource competence, ethical conduct and integrity of civil servants, the utilization of information technology in public services, and the implementation of a merit-based system in ASN management. Adequate competence enables civil servants to perform their duties optimally, while service ethics play a crucial role in fostering public trust. Furthermore, the adoption of digital technology has proven effective in enhancing service efficiency and transparency, whereas the merit system promotes objectivity and fairness in career development. The implications of this study highlight the necessity of continuously strengthening ASN professionalism through capacity building, ethical development, and adaptive bureaucratic reforms in response to contemporary challenges. Therefore, ASN professionalism serves as a vital foundation for achieving high-quality public services oriented toward public satisfaction.